An Evaluation of the Effects of Interest Rate Spread on Bank Performance: The Case of China - Chirapa, Tafadzwa Amanda G. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Interest rate spread is the difference between the interest rate received and the interest rate paid. This thesis seeks to investigate the relationship between the bank performance and the interest rate spread. The study focused on China and data was collected from The Bankers Database for the years 2014-2016. In order to analyse the relationship five independent variables were selected to assist in the research. These variables are interest rate spread, savings deposit rate, liquidity risk, operations risk and provision for bad debts. From the results we are able to conclude that there is a positive relationship between the interest rate spread and bank performance.

ÖZ: Faiz oranları farkı alınan faiz miktarı ve ödenen faiz miktarı arasindaki farktır. Bu tezin amacı Çin bankacılık sektörü performansı ile faiz oranları farkı arasındaki ilişkiyi incelemektir. Veri seti 2014-2016 yılları arasında olup bankacılar veri tabanından toplanmıştır. Bu tezde 5 değişken kullanılmıştır. Bunlar sırasıyla faiz oranları farkı, tassaruf mevduatı oranı, likidite riski, operasyonel risk ve takipteki kredilerdir. Bu tezin sonucunda faiz oranları farkı ile bankacılık sektörü performansı arasında istatistiksel olarak anlamlı pozitif bir ilişki bulunmaktadır.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2018. Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance; Banks and Banking--China; Interest rate spread; Bank performance